Chemistry : foundations and applications - Lagowski, J. J. (Macmillan Reference USA/Thomson/Gale, 2004)
"Although written for the high school student, this concise, readable, and authoritative source presents any science learner with a clear introduction to chemistry. The 480 entries cover all aspects of chemistry and its practical applications. A running glossary explains words as they are encountered in the text, and most entries have accompanying diagrams and photographs."--"Reference that rocks," American Libraries, May 2005.